Enhancing communication skills in english among secondary school students using cybernated storytelling : a case study - Roziana Mohamed Rosli (Kulliyyah of Education, International Islamic University Malaysia, 2017)
Storytelling is one of the most common activities used in teaching English proficiency to language students. In this investigation, the term 'cybernated storytelling' is introduced. The word 'cybernated' is coined from the word cyber, which means a computer-generated setting in the internet environment. Generally, storytelling activity requires a narration of the story in oral form, and sometimes aided by audio-visual elements. Storytelling can also be used to enhance students' communication skills. Upon listening to a story, students are anxious to share the stories and relate it to their own experience. It is widely accepted as a teaching technique by many educators because it engages students in learning. The aim of this study is to find out how cybernated storytelling could help students to improve their communication skills. However, until recently, little attention has been attended to how storytelling activities that are shared in the cyber world can enhance students' communication skills. Thus, this study intends to fill the gap of the factors that contribute to the enhancement of students' language proficiency and communication skills as well as the factors that inhibit the developmental process of the skills. This qualitative study involved 35 students, selected based on purposive sampling technique, from a multi-ethnic secondary school in Malaysia. After having an initial exposure on cybernated storytelling video production, the students were divided into small groups and required to engage in developing a cybernated storytelling video for a period of 90 days using the English language. While engaging in the activity, students were expected to communicate in face-to-face meetings and in writing: WhatsApp (WA) and Facebook (FB) platforms. The interview responses which were collected during the group interview, WA and FB entries were compiled and analysed thematically. Based on the data analysis, seven new emerging themes were discovered in addition to the six pre-determined themes. Additionally, these new emerging themes are more specific than the pre-determined ones. It implies that the communication activities in the cybernated storytelling video production involved many factors that are interdependent of each other. In addition, there are positive outcomes that are derived from the cybernated storytelling activity: students expressed their increased confidence in using the target language, perceived improvement in their language competency and communication skills, increased frequency of language productivity in terms of speaking and writing outputs. Hence, the study implies that cybernated storytelling is meaningful and relevant in language courses that involve the Z generation in schools, theoretically and pedagogically. Suggestions for policy makers, school administrators, teachers, parents, and community are discussed in addition to recommendations for future research. Key words: Storytelling, Cybernated, WhatsApp, Facebook, Communication skills